Too Few Indians and Too Many Chiefs. Is This One Reason for Declining Trade Union Membership in Denmark? - Voxted, Søren; Lind, Jens (Nordic Journal of Working Life Studies, 2012)
The decline in trade union membership in many countries since the 1970s and the consequent weakening of the trade unions is due to a number of reasons, including occupational changes, welfare state and social regulation, liberalism and individualization, and in Denmark (and Sweden and Finland) changes in unemployment insurance legislation and the institutional settings of the unemployment insurance system. All these factors are well known and have been analyzed in the literature. This article sums up all these facts and reasons for trade union decline in Denmark, but the main analysis focuses on a supplementary reason for membership decline among LO (the Danish Confederation of Trade Unions)-affiliated unions: many trade union members leave their unions to become members of unions that organize managers. When workers become managers, some prefer to join an organization expert in servicing managerial staff, while others leave their trade unions because they define themselves as managers without being formally appointed as such and without having formal managerial responsibilities. Reasons for this behavior will be discussed in the article.